O pensameto político de Claúdio Manuel da Costa: uma leitura do poema Vila Rica - Diva Teixeira Viveiros (2009)
The objective of this paper is to propose a rereading of the epic Vila Rica written byCláudio Manuel da Costa in 1773 which was only published in 1839. There were feweditions of the poem in more than two hundred years of its composition and littlerecognition for its literary quality and historic importance. Vila Rica as a fruit of the pen ofthe greatest luso-brazilian writer from the seventieth century deserves to have itsimportance reconsidered in the Brazilian historical and literary studies. The purpose of thispaper is to contribute to the analysis of the poem under the perspective of Claudio Manuelda Costas mythical reading about the origins of Minas Gerais Captainship. As he reclaimsthe mythical foundation of the Captainship, Claudio Manuel da Costa introduces his modelof good management, of a fair king and of society based on the second scholastic and acorporate view of State.